Factors influencing customer acceptance towards food biotechnology products: a case study at Mardi / Norraeffa Md Taib and Ummi Kalsum Hassian - Md Taib, Norraeffa; Hassian, Ummi Kalsum (Research Management Institute (RMI), 2012)
Biotechnology has been identified as the new mechanism of growth for Malaysian economics. Malaysia is one of the country rich with the natural resources for health care applications, food production, and solutions for a clean environment, then livestock farming, the herbal industry, and traditional and modern medicine. Biotechnology is an important tool practice to improve the quality of our life and has started to get acceptance among consumers in the food market. Food biotechnology already provided many benefits towards life-saving medicines, improving the nutrition of food, the taste, quality and also the freshness of various foods exist today. This study is carried out to identify the factors that influence the consumer's acceptance towards food biotechnology products practiced by Mardi. It is expected that the result will demonstrate influencing factors are significantly related with customer acceptance of food biotechnology product.